THE ROLES OF CIVIL SOCIETIES, GOVERNMENTAL AGENCIES AND CITIZENSHIP EDUCATION IN SUSTENANCE OF DEMOCRATIC GOVERNANCE IN NIGERIA - MAS’UD BELLO (International Studies Journal)
The cardinal goal of democracy and democratization in different parts of the globe is to address the aspirations of the people in all the constituencies that made its political entity. In Nigeria democratic governance has not produced the expected results of the dreams of Nigerian. Nigeria as a nation has made attempts since 1960 when it attained its political independence to establish durable democratic governance. The first attempt was parliamentary system and the transition to a presidential system in 1979. It has generally been assessed that only little have been delivered as a dividend of democracy in Nigeria because of institutional and human failure. Democratic system in Nigeria has been characterized by corruption, misplacement of priorities, wastages in governance and gross human rights violate, etc. This paper intends to examine the role of governmental agencies and nongovernmental organizations and citizenship education in the re-engineering and sustenance of democratic governance in Nigeria. The methodologies adopted include; reviews the use of primary and secondary sources and interdisciplinary approach.